ECTHR_COMMITTEE 28617/10 vom 13. November 2014 , AFFAIRE PATRIKIOS c. GRÈCE - Ecthr Committee (2014)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure administrative;Article 6-1 - Délai raisonnable); Violation: 6;6-1